ENHANCING VOCATIONAL HIGH SCHOOL STUDENTS' READING SKILLS USING JEOPARDY GAMES - Krisdianata, Yoannes Yuka; Kuswandono, Paulus (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Jeopardy game is a common game for players to compete for the highest score.  Nevertheless, this game can be modified to provide the students with a fun, engaging, and challenging interactive game for learning activities. The use of the Jeopardy game in improving teaching-learning activities was abundant, whereas the use of Jeopardy in vocational high school was little to be found. This study tried to figure out the implementation of Jeopardy games in enhancing reading skills for vocational high school students. Classroom action research was conducted to observe students' improvement in reading after implementing Jeopardy games in reading activities. Closed-ended questionnaires on how the jeopardy games influence the teaching process and activities were conducted to get the quantitative data. Observation, reflection, open-ended questionnaire, and FGD were gathered to strengthen the result of quantitative data. The results showed that students demonstrated better reading comprehension from the diagnostic test, cycle I, and cycle II results; mean score 5.76, 6.48, and 7.28. Students also reported that they got motivated and were likely to read more. To conclude, students stated that they experienced some improvement in cooperative learning and reading strategies. The implication of the study is discussed at the end of this article.